2003
DOI: 10.1103/physrevb.67.129903
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Electronic and transport properties of single-wall carbon nanotubes encapsulating fullerene-based structures [Phys. Rev. B64, 115409 (2001)]

Abstract: In the two lines immediately after Eq. ͑9͒ ␣ and ␤ should be read as ␣ϭ1ϩre i(ϩ2) , ␤ϭ1ϩre Ϫi2␦ , and in Eq. ͑10͒ ⌫ 0 should be read asThese corrections do not change the main results of the paper. We thank Stefan Rotter for pointing out the errors.PHYSICAL REVIEW B 67, 129903͑E͒ ͑2003͒

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…In this context, the present result is more similar to the case of semiconductor quantum structures [5][6][7] and agrees with the theoretical predictions. 8,9 Since a SWCNT is an ideal quantum wire with a diameter of approximately 1 nm, the shifts in the transverse field strongly suggest the occurrence of the QCSE in the SWCNT.…”
Section: ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the present result is more similar to the case of semiconductor quantum structures [5][6][7] and agrees with the theoretical predictions. 8,9 Since a SWCNT is an ideal quantum wire with a diameter of approximately 1 nm, the shifts in the transverse field strongly suggest the occurrence of the QCSE in the SWCNT.…”
Section: ͑1͒mentioning
confidence: 99%
“…[5][6][7] Since SWCNTs are ideal quantum wires, the QCSE in SWCNTs has been theoretically predicted. 8,9 However, the electricfield-induced optical changes in a SWCNT have never been investigated, because of the high conductance due to the contamination of metallic nanotubes. Recently, the fabrication of back-gated thin-film transistors ͑TFTs͒ has been reported and opened a way of applying spectroscopy to SWCNT as a function of gate voltage without a current flow.…”
mentioning
confidence: 99%
“…Theoretically, energy bands for commensurate DWCN's and/or MWCN's have been calculated and energy-level separation due to the intertube transfer [17,18,19,20] and result-ing reductions of the conductance have been reported [20,21]. For some incommensurate DWCN's, the density of states was calculated and a weak effect of the intertube transfer near the Fermi energy has been reported [22].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The most distinguishable feature of multiwall nanotubes is that interwall interactions exist between neighboring shells. Previous theoretical calculations have shown that interwall interactions drastically alter the electronic and transport properties of hybrid nanotube structures, such as pseudogap opening in the ͑5,5͒/͑10,10͒ double-wall nanotube, [9][10][11] antiresonances in nanotubes containing fullerene molecules, 12 and diffusive transport in incommensurate multiwall tubes. 13 Recent experiments 14 have reported that multishell transport is more likely to occur in multiwall nanotubes, contrary to the belief that the transport would be governed by the outermost shell.…”
mentioning
confidence: 99%